Improvement of Rice Straw Hydrolysate Preparation for Bioethanol Production Using Saccharomyces Cerevisiae ATCC 24860 - Roslan, Ahmad Muhaimin (2011)
Production of biological ethanol (bioethanol) from biomass waste residues through biotechnological approach (cellulosic bioethanol) is important nowadays as it is a mitigation process towards fossil fuel depletion, energy crisis and greenhouse gasses pollution. It is an environmental friendly process which also facilitates carbon sequestration and provides a carbon neutral fuel for transportation and other applications. It is also an alternative way to utilize biomass waste from agroindustries such as oil palm empty fruit bunches (OPEFB) and rice straw. In this study, cellulosic bioethanol was produced from rice straw through a three-stage system which are pretreatment of the rice straw, enzyme production and cellulosic bioethanol fermentation. The first stage is pretreatment, where improvements on existing pretreatment technologies were studied, without chemical treatment. Wet disc milling machine was used with the addition of water to the rice straw prior the milling process involving rotating grinding stones. By incorporating thermal treatment (121°C) to the wet discmilled product, there are improvements in free glucose released prior to enzymatic hydrolysis and reduction in lignocellulosic particle size. It was found that by wet disc milling and thermal treatment, 0.046 g glucose was released per g rice straw as compared to 0.024 g glucose per g rice straw respectively. While for NaOH pretreatment, no glucose release can be detected after pretreatment since the rice straw must be rinsed to remove the chemical. The second stage involves cellulase production and enzymatic hydrolysis of rice straw. By incorporating 50 mL of palm oil mill effluent (POME) as nutrient in 1 liter Mandel’s medium, cellulase production from rice straw by Aspergillus sp. at 30°C after 5 days produced remarkable activity, which is 6.3 FPU/g rice straw used. This crude cellulase when used on pretreated rice straw in 50 mL bottle with magnetic stirrer bar at pH 4.8 and temperature of 50°C gave higher glucose compared to nonthermal treated rice straw, with increment from 0.245 g glucose/g rice straw to 0.380 g glucose/g rice straw. The third stage involves ethanol fermentation by yeast, Saccharomyces cerevisiae ATCC 24860. The pH of the hydrolyzed rice straw was adjusted to 6.0 prior to the yeast inoculation. Incubation was carried out in 50 mL stirrer bottle at 37°C. Theoretically, one mole of glucose (180.16 g) will be converted into two moles of ethanol (92.14 g). In this study, 0.10 g ethanol/g rice straw obtained, which counted for 62.61% of bioethanol produced.